Is Ovarian Cancer Prevention Currently Still a recommendation of Our Grandparents? - Millena Prata Jammal; Cid Almeida de Lima; Eddie Fernando Candido Murta; Rosekeila Simões Nomelini (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Ovarian cancer is the leading cause of death among gynecologic tumors because in most of the cases (75%), the disease is diagnosed in advanced stages. Screening methods are not available since the disease is rare, and the tested methods, such as ultrasound and CA125, were not able to decrease the mortality rate for this type of cancer. This article discusses the main risk factors for ovarian cancer, and the potential clinical and surgical strategies for the prevention of this disease.